OPTIMALISASI PERAN GURU PENDIDIKAN ANAK USIA DINI YANG PROPORSIONAL - Basri, Hasan (Institut Agama Islam Negeri Bone, 2019)
At this present time, Eealy Chilhood Education is a fundamental and strategic stage of education in human resource development, and the existence is needed in the community. This paper aimed to discuss the optimization ofÂ Proportional Role of Early Childhood Education Teachers. To optimize the role of the teacher, synergy is needed between the teacher, the companion, and the students. The proportional role of the ECE teachers is the balance and openness between students or their parents andthe teachers about their expectations versus the reality in educational institution.Keywords:Â Optimization, Early childhood education, ECE teacher, Proportional role.Â